2019
DOI: 10.1021/acs.nanolett.9b02220
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Macromolecular Pathways of IgG Oligomerization and Complement Activation on Antigenic Surfaces

Abstract: IgG antibodies play a central role in protection against pathogens by their ability to alert and activate the innate immune system. Here, we show that IgGs assemble into oligomers on antigenic surfaces through an ordered, Fc domain-mediated process that can be modulated by protein engineering. Using high-speed atomic force microscopy, we unraveled the molecular events of IgG oligomer formation on surfaces. IgG molecules were recruited from solution although assembly of monovalently binding molecules also occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(146 citation statements)
references
References 44 publications
(74 reference statements)
7
135
1
Order By: Relevance
“…In recent studies, the binding of C1q with IgG oligomers was studied, most notably by employing artificially hexamerized IgG antibodies [11][12][13][14]. It has been reported that IgG molecules have the potential ability to form hexamers in crystal or on mica surface under certain conditions [14,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent studies, the binding of C1q with IgG oligomers was studied, most notably by employing artificially hexamerized IgG antibodies [11][12][13][14]. It has been reported that IgG molecules have the potential ability to form hexamers in crystal or on mica surface under certain conditions [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Our STD data obtained by using a GM2 tetrasaccharide also confirmed that the interaction was significantly compromised by the removal of the outer galactose residue. In the subsequent experiments, we characterized the interaction of GB2 with GM1 in membrane environments (Figure 1c 13 C HSQC spectrum (black) and the 1 H-13 C STD-HSQC spectrum (red) of the 2-trimethylsilylethyl derivatives of the GM2 tetrasaccharide (10 equiv.) with 50 μM GB2.…”
Section: Epitope Mapping Of Gb2mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for example, two Abs, nominally to the same epitope, may well have somewhat different angles of approach to their target and may present a somewhat different array of Fcs to an effector cell with potential differences in effector function. For example, the importance of Ab arrays is suggested to be critical in complement triggering (Diebolder et al, 2014;Strasser et al, 2019). Furthermore, this discussion refers to mAbs.…”
mentioning
confidence: 99%